МОДЕРНИЗАЦИЯ СИСТЕМЫ ОБРАЗОВАНИЯ В СОВРЕМЕННОМ УЗБЕКИСТАНЕ - Таджимова, Ш.Р. (SCIENCE and SOCIETY, 2021)
The basis of improving of education system in our republic is the transformation of the essence of the education system, also its formation on the basis of assimilation and application of progressive experience of developed countries, the usage of effective methods and new pedagogical technologies. One of such modernized foreign technologies is credit-modular system. Credit–modular training system is such an organization of the educational process which is based on the combination of modular training technologies and credit educational units (credits).
Keywords: education system; credit technology; traditional training; credit-modular system; ECTS system; Bologna declaration